TINDAK TUTUR GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS VII TUNAGRAHITA SMPLB DHARMA WANITA PERSATUAN PROVINSI BENGKULU - Hardiyanti Fitria Rukmana; Suryadi Suryadi; Irma Diani (Jurnal Korpus, 2017)
The purpose of this research to describe the form of speech acts Ilocution used by teachers in learning Indonesian in class VII Mentally Disabled SMPLB Dharma Wanita Persatuan Bengkulu Province. The method used in this research is descriptive qualitative method. Sources of data in this study are teachers who teach Indonesian in grade VII Mentally Disabled. The data in this research is speech acts used by teachers. Data collection techniques in this research with methods refer, record and record. The data analysis technique in this research is done by the steps: (1) Listening and recording the learning process, (2) transcribing the recording, (3) coding the data, (4) classifying the data, (5) analyzing the data and (6) Concluded. Test the validity of the data using a credibility test that is by increasing perseverance and discussion with peers. The results of this research found several types of speech acts are assertiveness include acts declaring with variations of information (45 speech), states notices (20 speeches), states examples (4 speeches) and states justification (29 speeches) Then also found acts recognize (3 utterances ), Acts of appointment (37 speeches), act of defending (12 speeches), acts mention (3 speeches), acts of argument (7 speech) and acts of greeting (7 speech). Further directive includes questioning (184 speeches), command (83) speech, permits (38 speeches), prohibits (5 speeches), advises (6 speeches), and requests (7 speeches). Then found expressive include the act of praising (1 speech), criticizing (31 speech), complaining (1 speech), insinuating (7 speech), blaming (15 speech), thanking (1 speech) and declarative covering decision (5 speech). The speech acts used by the teacher differ from the speech acts used by teachers in the public schools, there are many repetitions of the act. In the repetition of such acts there is the use of two languages namely the Indonesian language and Bengkulu language, the use of match words and the use of fishing techniques. This is done by teachers so that students who have intellectual barriers are able to understand well every intention of the speech acts delivered by the teacher.